2010
DOI: 10.1515/pteridines.2010.21.1.87
|View full text |Cite
|
Sign up to set email alerts
|

Urinary Neopterin, Serum Retinol, α-tocopherol and Homocysteine in Breast Cancer Patients During Treatment with Bevacizumab and Chemotherapy

Abstract: Bevacizumab, monoclonal antibody targeting vascular endothelial growth factor, is effective in different tumors, including colorectal carcinoma, non-small cell lung cancer, renal cell carcinoma and breast cancer. Increased serum or urinary concentrations of neopterin, an indicator of systemic immune response, have been described in patients with tumors of different primary locations, and further increase has been observed during anticancer therapy. An increase of urinary neopterin has been described after admi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…The fact that most VEGF in the tumor microenvironment is considered to originate from tumorassociated macrophages could constitute a plausible link between high urinary neopterin levels and proangiogenic subtype ovarian cancers. The findings of Melichar et al [23] also indicate a link between VEGF and urinary neopterin.…”
Section: Discussionmentioning
confidence: 85%
“…The fact that most VEGF in the tumor microenvironment is considered to originate from tumorassociated macrophages could constitute a plausible link between high urinary neopterin levels and proangiogenic subtype ovarian cancers. The findings of Melichar et al [23] also indicate a link between VEGF and urinary neopterin.…”
Section: Discussionmentioning
confidence: 85%
“…88 Surprisingly, some in vitro and in vivo studies reported that bevacizumab could treat atherosclerosis by inhibiting neovascularization and decreasing total and LDL cholesterol and homocysteine. 89,90 However, some researches reported that systemic VEGF inhibition accelerated atherosclerosis, disrupted endothelial homeostasis, and increased hypertension and arterial thrombotic events. 91,92 Some scientists attempted to use special carriers to transport drug to atheromatous sites precisely.…”
Section: Discussionmentioning
confidence: 99%
“…Both points of view bring scientific arguments and, against the fact that the controversy continues, it is generally accepted that homocysteine is involved in vascular endothelial dysfunction and promotes thrombosis [41][42][43]. The literature mentions many diseases in which elevated homocysteine concentrations have been found in the blood: cardiovascular diseases [36,[44][45][46][47][48], neurological diseases [49][50][51][52], miscarriage [53][54][55], thrombophilia [56][57][58][59][60][61], bone fragility [62][63][64][65][66][67], diabetes [68][69][70][71][72][73][74], inflammation [75][76][77].…”
Section: Homocysteine and Pregnancy Complicationmentioning
confidence: 99%